Paired Rheumatoid Arthritis Synovial Biopsies From Small and Large Joints Show Similar Global Transcriptomic Patterns With Enrichment of Private Specificity TCRB and TCR Signaling Pathways - Triaille, Clement; Vansteenkiste, Louise; Constant, Manuel; Ambroise, Jérôme; Méric de Bellefon, Laurent; Nzeusseu Toukap, Adrien; Sokolova, Tatiana; Galant, Christine; Coulie, Pierre; Carrasco, Javier; Durez, Patrick; Lauwerys, Bernard R. (Frontiers in Immunology, 2020)
Objectives. We explored histological and transcriptomic profiles of paired synovial biopsies from rheumatoid arthritis (RA) patients, in order to assess homogeneity in synovial tissue at the individual level. Methods. Synovial biopsies were performed simultaneously in one small and one large joint per patient using needle-arthroscopy for the knee and ultrasound-guided biopsy for the hand or wrist. Synovium from individuals with osteoarthritis was used as controls. Paraffin-embedded samples were stained for CD3, CD20 and CD68. Total RNA was hybridized on high-density microarrays. TCRB variable sequences were obtained from synovial and blood RNA samples. Results. Twenty paired biopsies from 10 RA patients with active disease were analyzed. Semi-quantification of histological markers showed a positive correlation for synovial hyperplasia, inflammatory infiltrates and CD3-positive T cells between pairs. Pairwise comparison of transcriptomic profiles showed similar expression of RA-related molecular pathways (TCR signaling, T cell costimulation and response to TNF⍺). T cells clonotypes were enriched in all but one joints compared to blood, regardless of the magnitude of T cell infiltration. Enriched clonotypes were shared between pairs (23-100%), but this was less the case in pairs of joints displaying weaker T cell signatures and more pronounced germinal center-like transcriptomic profiles. Conclusion. Cellular and molecular alterations in RA synovitis are similar between small and large joints from the same patient. Interindividual differences in magnitude of T cell infiltrates and distribution of enriched T cell clonotypes support the concept of distinct synovial pathotypes in RA that are associated with systemic versus local antigen-driven activation of T cells.